THE POTENTIAL OF LOCALLY ISOLATED MICROALGAE IN LIPID PRODUCTION - LAM, DUONG BICH NGOC (2013)
Microalgae is fast becoming a promising biofuel feedstock due to their high lipid content and fast growing rate. However, the prospect of using microalgae in biofuel production needs extensive research as its potential sorely depends on the type of strain. This study therefore focuses on locally isolated microalgae to determine their potential in lipid production and carbon dioxide fixation. The freshwater samples were extracted from various locations in Malaysia which are at the Perak River, a pond at Universiti Teknologi Petronas (UTP) Mosque, and a lake in front of UTP. After performing microscopic observation, one strain of local microalgae which is referred to as BA due to its similar characteristics to the Botrydiopsis Arrhiza species is chosen for comparison with a commercial alga- Chlorella Fusca (CF) on growth, lipid content and carbon dioxide fixation.